Functional genomics approaches to cereal-aphid interactions - van Eck, Leon, author; Lapitan, Nora L. V., advisor; Botha, Anna-Maria, committee member; Leach, Jan E., committee member; Reese, John C., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: functional genomics; gene silencing; proteomics; transcription factors; wheat; Russian wheat aphid